PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA “MINITIM KABAR” UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Zania Ramadani; Wuli Oktiningrum (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
Weight measurement mathematics was an important material for weighing objects in everyday life. Based on the resulted of observations of students' scores on weight measurement 58% did not reach the KKM (Minimum Completeness Criteria). This study aim to (1) developing Minitim Kabar media for 2nd grade; (2) knowing the feasibility of “Minitim Kabar